Faʿāliyah al-Ḥiṣṣah al-Dirāsiyyah fī Taʿlīm ʿan Buʿd Kitāb al-Ḥadith al-Awwal bi Jāmiʿah ʿAliy bin Abī Ṭālib al-Islāmiyyah bi Surabaya al-ʿĀm al-Dirāsiy 2020-2021 al-Awwal fī Zamani Jāʾihah Corona - Endro Wibowo (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2021)
The new coronavirus pandemic has forced STAI Ali bin Abi Thalib Surabaya to close face-to-face learning in class and change the learning model to distance learning via the internet. The purpose of this study was to determine the effectiveness of the duration of face-to-face online lecture for learning hadits awwal course at STAI Ali bin Abi Thalib Surabaya. This research is a quantitative research using an experimental approach using a control class and an experimental class. The students in control class had face-to-face online lectures via the zoom application about 50 minutes a week and they also had lecture assignments, meanwhile the students in experimental class have of face-to-face lectures online about 100 minutes a week without being given assignments. This study uses two variables, the first is the duration of lecture hours as the independent variable and the value of learning outcomes as the dependent variable. The data was processed using the independent sample t test with the help of the SPSS program. The results of the research show that H0 is rejected and Ha is accepted. Thus, it can be concluded that there is a significant difference between the average student learning outcomes in the control class and the experimental class where the experimental class learning outcomes have a higher average learning outcome.